A Heteronomous Consumer Romance. (June 2020) - Molesworth, Mike
In the spirit of dystopian science fiction, this story imagines marketing in a near future. A reader might recognise that there is a relationship between aesthetic forms (stories) and the dramas that play out in society and so although this is fiction, it is also about the critical concerns that are emerging in the use of corporate technologies. The story draws from theory that suggests our most intimate relationships are embedded in and create market structures, and on theory that accounts for how technology (and especially AI) has significant impact on market practices. Core ideas also reference my previous and ongoing research on the imagination, on marketplace relationships and on digital virtual consumption, and from previous accounts of AI and market/political systems in speculative fictions. I invite the reader to reflect on the sorts of dominating human–technology–market relationships that may be with us soon, and on the risk of perverse instantiations in commercial AI deployment. Overall the tone is critical, but themes are also presented as ambiguous, recognising the seductive quality of marketing technologies.